The safety and efficacy of nasobiliary drainage in the treatment of refractory cholestatic pruritus: a multicentre European study. Issue 2 (2nd November 2015) - Hegade, V. S.; Krawczyk, M.; Kremer, A. E.; Kuczka, J.; Gaouar, F.; Kuiper, E. M. M.; van Buuren, H. R.; Lammert, F.; Corpechot, C.; Jones, D. E. J.
Summary: Background: Pruritus is a common symptom associated with cholestatic liver diseases. To date only small single centre case series have suggested efficacy of nasobiliary drainage in relieving cholestatic pruritus. Aim: To perform a multicentre study to evaluate the safety and efficacy of nasobiliary drainage in cholestatic pruritus. Methods: This was a retrospective study of all patients treated with nasobiliary drainage for refractory cholestatic pruritus between 2006 and 2015 at five European centres. Pruritus was quantified using a visual analogue scale (VAS) and liver enzymes, serum bilirubin and total serum bile salts (TBS) were measured before (pre‐NBD) and after nasobiliary drainage (post‐NBD). We analysed the duration of treatment response and associated complications. Results: In total, 27 patients (59% females) underwent 29 nasobiliary drainage procedures. The median duration of NBD was 7 days. NBD decreased pruritus in 89.6% of cases (VAS from 10.0 to 0.3, P < 0.0001). The median percentage decline in pruritus VAS was 94% and 33% of patients were free of pruritus within 24 h of starting drainage. The duration of treatment response was independent of duration of drainage ( P = 0.12) and bile output. Significant improvements were seen in the median levels of serum alkaline phosphatase ( P = 0.001) and serum bilirubin ( P = 0.03) but not in serum TBS ( P = 0.07). Mild post‐endoscopic retrograde cholangiopancreatography pancreatitis (31%) was the most frequent complication. Conclusions: Nasobiliary drainage is effective in relieving cholestatic pruritus in most patients and has favourable effect on biomarkers of cholestasis. Nasobiliary drainage may be associated with high risk of adverse events, especially pancreatitis. Prospective studies are needed to confirm our findings.